MANET에서 악의적 노드 탐지율 향상을 위한 협업모델 설계 - 신언석(Eon-Seok Shin); 전서인(Seo-In Jeon); 박건우(Gun-Woo Park); 류근호(Keun-Ho Ryu) (韓國컴퓨터情報學會論文誌, 2013)
MANET has a weak point because it allows access from not only legal nodes but also illegal nodes. Most of the MANET researches had been focused on attack on routing path or packet forwarding. Nevertheless, there are insuffcient studies on a comprehensive approach to detect various attacks on malicious nodes at packet forwarding processes. In this paper, we propose a technique, named DTecBC (detection technique of malicious node behaviors based on collaboration), which can handle more effciently various types of malicious node attacks on MANET environment. The DTecBC is designed to detect malicious nodes by communication between neighboring nodes, and manage malicious nodes using a maintain table. OPNET tool was used to compare with Watchdog, CONFIDANT, SRRPPnT for verifying effectiveness of our approach. As a result, DTecBC detects various behaviors of malicious nodes more effectively than other techniques. MANET에서는 합법적인 노드와 비합법적인 노드 모두 네트워크에 접근이 가능함에 따라 보안 취약점을 안고 있다. MANET에 관한 대부분의 연구들은 라우팅 경로 또는 패킷 전달에 대한 공격 측면에만 중점을 두고 있으며, 특히 악의적인 노드의 다양한 공격에 효과적으로 대응하는데 한계가 있다. 이 논문에서는 MANET에서 다양한 악의적인 노드를 효율적으로 탐지하기 위한 DTecBC (detection technique of malicious node behaviors based on collaboration) 기법을 제안하였다. 제안 기법은 이웃 노드들 간의 협업관계를 기반으로 상호 메시지 교환을 통하여 악의적인 노드를 관리할 수 있도록 설계하였다.. 제안기법의 효율성 검증을 위해 OPNET 시뮬레이션 툴을 사용하여 기존의 대표적 탐지기법인 Watchdog, CONFIDANT, SRRPPnT와 비교하였다. 평가 결과, 제안 기법은 기존 기법들에 비해 다양한 유형의 악의적인 노드 행위를 종합적으로 탐지 가능함이 확인 되었다.